A survey of religious instruction in the public schools of Pangasinan and Dagupan City - Cayabyab, Alfredo Gelli 1915- (University of the Philippines], 1959)
The writer aims to find out whether in the implentation of the religious provision of our Constitution, there are factors that contribute to the alleged failure of religious instruction in the public schools of Pangasinan.